South polar skua (Catharacta maccormicki) as biovectors for long-range transport of persistent organic pollutants to Antarctica. (1st January 2022) - Wild, Seanan; Eulaers, Igor; Covaci, Adrian; Bossi, Rossana; Hawker, Darryl; Cropp, Roger; Southwell, Colin; Emmerson, Louise; Lepoint, Gilles; Eisenmann, Pascale; Nash, Susan Bengtson
Abstract: Migratory bird species may serve as vectors of contaminants to Antarctica through the local deposition of guano, egg abandonment, or mortality. To further investigate this chemical input pathway, we examined the contaminant burdens and profiles of the migratory South polar skua ( Catharacta maccormicki ) and compared them to the endemic Adélie penguin ( Pygoscelis adeliae ). A range of persistent organic pollutants were targeted in muscle and guano to facilitate differentiation of likely exposure pathways. A total of 56 of 65 targeted analytes were detected in both species, but there were clear profile and magnitude differences between the species. The South polar skua and Adélie penguin muscle tissue burdens were dominated by p, p′ -dichlorodiphenyldichloroethylene (mean 5600 ng g −1 lw and 330 ng g −1 lw respectively) and hexachlorobenzene (mean 2500 ng g −1 lw and 570 ng g −1 lw respectively), a chemical profile characteristic of the Antarctic and Southern Ocean region. Species profile differences, indicative of exposure at different latitudes, were observed for polychlorinated biphenyls (PCBs), with lower chlorinated congeners and deca-chlorinated PCB-209 detected in South polar Skua, but not in Adélie penguins. Notably, the more recently used perfluoroalkyl substances and the brominated flame retardants, hexabromocyclododecane and tetrabromobisphenol A, were detected in both species. This finding suggests local exposure, given the predicted slow and limited long-range environmental transport capacity of these compounds to the eastern Antarctic sector. Graphical abstract: Image 1 Highlights: Migratory vs resident Antarctic bird species showed distinct chemical profiles. Species' concentration differences reflected expected trophic level differences. Recently used Persistent Organic Pollutants were omnipresent in both species. Polychlorinated biphenyl profiles provided clearest differentiation of exposure.